The Influence of Productive Zakat, Business Capital, and Duration of Business on the Income Level of Mustahik at Baznas Jepara Regency - Umi Nabila Rosada; Mahmudatus Sadiyah (Al-Mashrof: Islamic Banking and Finance, 2025)
The purpose of this study was to test and analyze the effect of productive zakat, business capital, and length of business on the level of mustahik income at Baznas Jepara Regency. This study uses descriptive quantitative research methods. The population used is the recipient of the Jepara Makmur program from Baznas in 2023 as many as 1875 mustahiks. The sample in this study used the Slovin formula by taking a sample of 95 respondents. The sampling technique was carried out using the purpposive sampling method. Data collection techniques using a questionnaire measured by Likert scale measurements. The data analysis technique used is regression analysis with the help of the SPSS application. The results of this study indicate that the results show that the Productive Zakat variable has a positive and significant effect on Income Level. While the second hypothesis says that the business capital variable also has a positive and significant effect on the income level and the third hypothesis says that the length of business has a positive and significant effect on the income level. Based on the results of the F test, simultaneously the independent variables (Productive Zakat, Business Capital, and Length of Business) have a very significant effect on the dependent variable (Income Level) with an R Square value of 34.7%, while the remaining 65.3% is influenced by variables not included in this study.   Keywords: Income Level Of Mustahik, Productive Zakat, Business Capital, Length Of Business